(untitled) (Journal of Mathematics Mechanics and Computer Science, 2023)
In this work, a software module for calculating drill string displacements taking into account the effect of a drilling fluid flow, external loads and the intermittent contact of the drill string with the borehole wall is developed. A generalized nonlinear mathematical model of the drill string spatial lateral vibrations underlies the module. The V.V. Novozhilov nonlinear elasticity theory and the Ostrogradsky-Hamilton variation principle were used to derive the mathematical model. To create the software module, the universal Wolfram Language with integrated computational intelligence is utilized. The functions for performing 2D visualization of the drill string spatial displacements, constructing phase portraits of the solution and conducting the comparative analysis of the obtained numerical results are included into the module. The developed module allows predicting the dynamics of the drill string before the beginning of well drilling due to the possibility of pre-setting the parameters of the drilling system and accounting for the environmental factors in the process of modeling for ensuring quick, safe and efficient exploration and production of natural resources.